ANALISIS PENTAD TERHADAP DRAMATISME EMOSIONAL MENTERI SOSIAL REPUBLIK INDONESIA TRI RISMAHARINI - Insani Aulia Razan; Beta Ayodya (Jurnal Sosial-Politika, 2022)
Dramatism studies the language and its application to the audience. In drama, life problems are a source of motivation for the actions of the actors involved in it which reflect the character and thoughts, something cannot be said as drama without using a situation that contains a conflict. Drama is like a theatrical performance, it requires the presence of an actor. This study places the Minister of Social Affairs of the Republic of Indonesia Tri Rismaharini as the object of research. Inaugurated as social minister in the midst of the crisis of the Covid-19 pandemic, Risma has been faced with chaos in the social assistance data. This research is included in descriptive research. Data analysis was performed using pentad analysis from Kenneth Duva Burke. This research resulted in an identification of the rhetorical style of the Minister of Social Affairs, Tri Rismaharini. Risma presents herself in public as an emotional Minister. The weight of pentad in the activities of the Minister of Social Affairs of the Republic of Indonesia, Tri Rismaharini, lies in the agency and the scene. Even though Risma is a politician who is known to be angry and fierce, Risma goes through various scenes to achieve the realization of good governance.Keywords : Dramatism, Risma, Angry, Rhetoric.